Harmonizing Lifestyle and Environment in the Digital Era: A Framework for Sustainable Living (LiFE) - Simon, Lila; Thomas, Sheena (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
A “sustainable lifestyle” is a cluster of habits and patterns of behavior embedded in a society and facilitated by institutions, norms and infrastructures that frame individual choice, in order to minimize the use of natural resources and generation of wastes, while supporting fairness and prosperity for all. India is a young country with 50% of its population below the age of 25. The choices of the youth and their Lifestyle indeed shapes the economy of any country. At this juncture when India aims to be in the league of developed countries by 2047, it’s important to understand the mindset of the youth towards protecting the environment and promoting sustainable development especially in the digital era. The vision of LiFE is to live a lifestyle that is in tune with our planet and does not harm it. The purpose of the study was to understand the behavior of the youth towards Lifestyle for Environment (LiFE) particularly in domains of Energy consumption, water management, and buying sustainable products. A Self-reported questionnaire was prepared on LiFE and data was collected from 350 youths in central India. The data was analyzed using percentage. The results indicate that the youth values the environment and takes measures to reduce, reuse and recycle the consumptions.